Solving optimisation problems using computer software - Wong, Sarah Elita Shi Yuan (2018)
This report contains a summary and comparison of some of the different approaches which have been used to formulate and solve single-depot Vehicle Routing Problems (VRPs). The approaches studied in this report consist of exact approaches (Transformation of VRP to TSP and Branch-and-bound method), some of the more popular heuristic approaches (Clarke and Wright Savings Algorithm, Holmes and Parker, Fisher and Jaikumar), and a metaheuristic (Genetic Algorithm). In this project, we test out the applications of the combination of “Transformation of VRP to TSP” with Genetic Algorithm and to Microsoft Excel Solver, and “Vehicle Flow Formulation combined with Simplex Method” to obtain solutions for a single-depot VRP.